2010
DOI: 10.1002/humu.21301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lynch syndrome mutations in the MLH1-PMS2 interface that disturb dimerization and mismatch repair

Abstract: Missense alterations of the mismatch repair gene MLH1 have been identified in a significant proportion of individuals suspected of having Lynch syndrome, a hereditary syndrome that predisposes for cancer of colon and endometrium. The pathogenicity of many of these alterations, however, is unclear. A number of MLH1 alterations are located in the C-terminal domain (CTD) of MLH1, which is responsible for constitutive dimerization with PMS2. We analyzed which alterations may result in pathogenic effects due to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 41 publications
4
55
1
Order By: Relevance
“…Guerrette et al 43 45 Bianchi et al, 29 and Kosinski et al 46 found normal MLH1-PMS2 in vitro binding activity in their studies. Raevaara et al 45 also performed other in vitro MLH1 protein functional studies, including protein expression and stability, subcellular localization, protein-protein interaction, and repair efficiency.…”
Section: Functional Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…Guerrette et al 43 45 Bianchi et al, 29 and Kosinski et al 46 found normal MLH1-PMS2 in vitro binding activity in their studies. Raevaara et al 45 also performed other in vitro MLH1 protein functional studies, including protein expression and stability, subcellular localization, protein-protein interaction, and repair efficiency.…”
Section: Functional Studiesmentioning
confidence: 86%
“…The first three studies (Guerrette et al, 43 Kondo et al, 44 and Belvederesi et al 28 ) show that the K618A variant has substantially lower ability to bind PMS2, but that it still binds a nontrivial fraction of the available PMS2. The studies by Raevaara et al 45 and Kosinski et al, 46 however, showed no difference between K618A and wild-type MLH1 constructs with respect to PMS2 binding. The Raevaara group used a method quite different from those of the other four studies, one that may not be able to distinguish between normal and reduced binding.…”
Section: In Silico Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…It has been previously reported that terminal MLH1 defects prevent the formation of a stable complex with PMS2, resulting in an impaired DNA mismatch repair function [6,9]. Although dimerization is not required for nuclear localization, the MLH1-PMS2 heterodimer is imported in the nucleus more efficiently than either MLH1 or PMS2 monomers [57].…”
Section: Discussionmentioning
confidence: 99%
“…Germline mutations in MLH1 have been identified throughout the entire gene, and are frequently located in the ATP binding domain and in the C-terminal region which is responsible for constitutive dimerization with the PMS2 protein [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%